Breast Cancer in Young Women: Analysis of Incidence, Clinicopathological Profile and Biological Behaviour in a Tertiary Care Institute from South India - B, Sai Sanmathi; Narayanan, Geeta S; PS, Amogh; BR, Kiran Kumar (Asian Pacific Journal of Cancer Biology, 2024)
Aims and Objectives: There is an increasing incidence of breast cancer in young women and many of these patients are considered to have more aggressive disease biology. The study aimed to find out the demographic profile, clinicopathological profile, and management details in patients under the age of 40 years treated for breast cancer in a tertiary care institute. Materials and Methods: The study retrospectively analysed all the females with biopsy proven breast cancer treated at our oncology department between January 2012 and December 2018. Patients aged below 40 years were stratified from the total breast cancer patients. The data related to demographic profile, clinical staging, pathological staging, hormonal status and treatment details were collected from medical records for the patients and analysed. Results: A total of 1056 biopsy proven breast cancer patients were treated during the study period. Out of which, the breast cancer patients under the age of 40 years were 161 (15.24%). The mean age at presentation was 33 years. Maximum patients were between the age group of 35 to 40 years (45.4%). Most of the patients were presented with Stage III (44%). Infiltrating Ductal Carcinoma, Grade II was the most common histologic type and grade. ER (Oestrogen Receptor) positivity seen in 49% of patients and PR (Progesterone receptor) Positivity in 49.7% and 46% had HeR2 Positivity. Conclusion: Our study concludes that the incidence of breast cancer patients under the age of 40 years is increasing. These patients tend to have higher grade tumours, Her2 Positive and triple-negative breast cancer. Young patients presenting with breast lumps should undergo all standard screening and diagnostic investigations must be carried out for early diagnosis and proper interventions.